Constitutive and heat-inducible heat shock element binding activities of heat shock factor in a group of filamentous fungi - Xavier, Ilungo J. (Cell Stress Society International, 1999)
This study represents the initial characterization of the heat shock factor (HSF) in filamentous fungi. We demonstrate that HSFs from Beauveria bassiana, Metarhizium anisopliae, Tolypocladium nivea, Paecilomyces farinosus, and Verticillium lecanii bind to the heat shock element (HSE) constitutively (non-shocked), and that heat shock resulted in increased quantities and decreased mobility of HSF-HSE complexes. The monomeric molecular mass of both heat-induced and constitutive HSFs was determined to be 85.8 kDa by UV-crosslinking and the apparent molecular masses of the native HSF-HSE complexes as determined by pore exclusion gradient gel electrophoresis was 260 and 300 kDa, respectively. Proteolytic band clipping assays using trypsin and chymotrypsin revealed an identical partial cleavage profile for constitutive and heat-induced HSF-HSE complexes. Thus, it appears that both constitutive and heat-inducible complexes are formed by trimers composed of the same HSF molecule which undergoes conformational changes during heat shock. The mobility difference between the complexes was not abolished by enzymatic dephosphorylation and deglycosylation, indicating that the reduced mobility of the heat-induced HSF is probably due to a post-translational modification other than phosphorylation or glycosylation.